Mengidentifikasi Strategi Pembagian dari Calon Guru Sekolah Dasar - Puri Pramudiani; Yoppy Wahyu Purnomo; Tian Abdul Aziz (Universitas Muhammadiyah Prof. Dr. HAMKA Press, 2016)
This study focuses on identifying pre-service primary school teachers’ works with division problem using a mathematical approach called Realistic Mathematics Education (RME). A case study was conducted to thirty-six pre-service primary school teachers in one private university in Jakarta who took RME course. The result of analysis of the participants' written responses indicates that the approach led the participants to develop mathematical meaning to deal with division problems by means of various strategies. In compliance with the tenets of RME, to wit, the use of model and symbol for progressive mathematization, the study shows that the participants could acquire orientation for developing their mathematical ideas and strategies. Implications of the findings are discussed.